Study of the effects of Trigonella foenum graecum and Elettaria cardamom against Tribolium Castaneum - Mohammed, Manal Dheyaa’; Eissa , Ahmed Ali; Abduljaleel, Raghad Dhiyaa’ (Iraqi Journal of Science, 2022)
Oils were extracted from seeds of Trigonella foenum graecum as well as from seeds of Elettaria cardamomum, then separated and characterized by Gas Chromatography with Mass spectra GC/MC twelve different compounds of Trigonella foenum graecum oil were identified, the highest rate was for the compound 9, 12-Octadecadienoic acid (Z,Z) which was found with rate of 38.97،%then accompanied with 31.85% of 9-Octadecenoic acid (Z)-, methyl ester.On other hand fifty four (54) different compounds were separated from fixed oils of Elettaria cardamomum , the highest rate for the compound 3-Cyclohexene-1-methanol, .alpha.,.alpha.,4-trimethyl-, acetate which was 22.88% then the compound Butyl 9,12-octadecadienoate with a rate of 21.22 % .The lethal effect of oils against Tribolium castaneum was studied for several periods, the results clarify that the oils of Trigonella foenum graecum and Elettaria cardamomum , significant effects on insect mortality reached to (96.9 and 92.5 )% when they were used with concentration 700 ppm after72 hours of treatment.